Contribuição ao estudo anatômico das Myrtaceae nativas no Rio Grande do Sul - Santos, Sidinei Rodrigues dos (2012)
Myrtaceae is one of the most important botanical families, either in diversity and species abundance, in different forest types on Rio Grande do Sul State, Brazil. Very complex from the taxonomic point of view, this family has experienced important modifications in their internal arrangement. Recent phylogenetic studies gave an important step toward clarifying the true relationship between different taxa, but some questions still remain. In the present work was studied the wood anatomy of 26 species, related to 13 distinct genera of Myrtaceae from Rio Grande do Sul State (Brazil), as an alternative to solving internal taxonomic problems in the family. The wood samples were gained in the Forest Sciences Department wood collection, of the Federal University of Santa Maria, and by field collections specially realized to the present investigation. The wood descriptions followed the recommendations of the IAWA Committee (1989). A great structural homogeneity was observed in the studied material, reflecting the high number of shared anatomical features (diffuse porosity; solitary pores; simple perforation plates; appendices (tails); alternate intervessel pits; vessel-ray pits similar to intervessel pits; apotracheal diffuse and diffuse-in-aggregates parenchyma, always seriated; heterogeneous rays; fibres with bordered pits; and disjunctive ray-cells). Due to lack of particular anatomical features, none genera could be identified based on wood anatomy, with the only exception of Myceugenia; the species, however, can be separated, but not always. Infratribe taxonomic categories can t also be identified due to the absence of particular anatomical features. The lack of specific anatomical features to genera and higher taxonomic groups limits the use of wood anatomy in Myrteae taxonomic studies.